Measuring the Channels of Monetary Policy Transmission: A Factor-Augmented Vector Autoregressive (Favar) Approach - Dawit Senbet (Journal of Central Banking Theory and Practice, 2016)
There is more consensus on the effects of monetary policy than its transmission mechanism. Two channels of transmission mechanisms are the conventional interest rate channel and the credit channel. I investigate the channels of monetary policy transmission in the U.S. using the factor-augmented vector autoregressive (FAVAR) models developed by Bernanke, Boivin & Eliasz (2005). The newly developed FAVAR approach allows the researcher to include all relevant macroeconomic variables in the model and analyze them. Therefore, the FAVAR models span a larger information set and generate better estimates of impulse response functions than the commonly used vector autoregressive (VAR) models that utilize only 4–8 variables. I include 154 monthly U.S. time series variables for the period 1970–2014. The findings support the existence of the credit channel in the U.S. The conclusion remains the same when the nonborrowed reserve operating regime (October 1979–October 1982) is removed from the sample period.
Keywords: E52; E58; C32; C43; 330; Monetary policy; Credit channel; Interest rate channel; Dynamic factors; VAR; FAVAR; Impulse response functions.